Briaviodiols B–E, new anti-inflammatory hydroperoxyfurancembranoids from Briareum violaceum. Issue 7 (15th February 2019) - Huang, Pin-Chang; Tseng, Chung-Chih; Peng, Bo-Rong; Hu, Chiung-Chih; Lin, Nai-Cheng; Chen, Nan-Fu; Chen, Jih-Jung; Wen, Zhi-Hong; Wu, Yang-Chang; Sung, Ping-Jyun
Abstract: Four new hydroperoxyfurancembranoids, briaviodiols B–E (1 –4 ), were obtained from an octocoral identified as Briareum violaceum . The structures of cembranoids 1 –4 were established by using spectroscopic methods and comparing the spectroscopic data with those of known related analogues. Compounds 1, 3, and 4 were found to exhibit significant in vitro anti-inflammatory activity in LPS-induced RAW 264.7 macrophage cells by inhibiting the expression of iNOS protein. Graphical abstract: